"Match Analysis" using notational analysis and data analytics in table tennis with interactive visualisation - Gambhir, M. (Proceedings Book of The 16th ITTF Sports Science Congress Budapest (HUN), April 19th - 20th, 2019, 2020)
Asia has supremacy over World Table Tennis, with China in particular. Withal technical, physical, mental training in place, one crucial aspect they work on is "Specificities"! With more and more science and technology permeating sports, Notational Analysis is an empirical method that collects objective data, analyses player`s performance and helps coaches to work on specificities. Franks and Millers, during research (in 1986, 1991), stated that post a match, coaches can recollect only 30% of the key factors that determine performance. Thus, capturing objective data and analyzing a match plays a pivotal role in determining an athlete`s performance. The aim of this paper is to explain how advance data analytics is applied to notation analysis for creating "in-depth match analysis" solution and "athlete profiling". The in-depth "match analysis" solution, delves into every minuscule aspect of an athlete`s performance, be it technical or tactical. Many matches have been analyzed for amateur and professional athletes from India, Junior & youth primarily during this study. The results from this match analysis were remarkable and the feedback from coaches was very encouraging. Further, a collection of the large set of athlete`s data converges to "athlete profiling" that asserts trends, track patterns, errors and progress. This helps coaches in understanding the profound mistakes and anomalies of the players and planning a very specific training program accordingly. Additionally, player`s reviews were also captured post their matches to substantiate discrepancies, if any. It is not strange but interesting that 80% of the players had presumptions about their performance that don`t conform with match analysis. Such disparities clearly depict a strong role of in-depth match analysis and athlete profiling in redressing player`s presumptions and apprehensions. Of course, the real value of notational analysis is not only in being able to measure performance but in delivering a blueprint to develop a specific training plan with a clear roadmap. Unlike traditional coaching, it is indispensable in assisting coaches and players in developing measurable improvements in their game skills.